Intertextuality as textual practice in Zimbabwean religious discourses: a textual analysis of the founding text of the African Apostolic Church - Manyawu, Andrew Tichaenzana (Routledge, 2021)
This article discusses ways in which African Apostolic Church founder, Paul Mwazha, an indigenous Zimbabwean religious leader, has taken advantage of the linguistic resources available to him to attain specific rhetorical goals. It is concerned with the discursive relation between the Shona and English versions of his two-volume founding text titled, in Shona, Kutumwa kwaPaul Mwazha we Africa and, in English, The Divine Commission of Paul Mwazha of Africa. The article deconstructs that relationship in terms of Mwazha’s use of intertextuality as textual strategy in the context of his rhetorical goal of building up Apostolic African Instituted Church (AAIC) spiritual practice as the inevitable choice of every true Christian believer. It is argued that Mwazha has treated the linguistic need for an English version of his founding text as an opportunity to not only address the needs of an audience different from that of his initial Shona text, but also draw on various intertextual strategies to adjust aspects of the message of his Shona text in light of new thinking about his spirituality and the dynamic socio-cultural context of his teaching. The English version of the founding text thus becomes an intertextual discursive event illustrative of the pragmatic imperative underpinning Mwazha’s rhetoric.